THE INFLUENCE OF HUMAN RESOURCE COMPETENCE, THE APPLICATION OF REGIONAL FINANCIAL ACCOUNTING SYSTEMS, THE USE OF INFORMATION TECHNOLOGY, THE ROLE OF INTERNAL AUDIT, AND INTERNAL CONTROL SYSTEM FOR QUALITY LOCAL GOVERNMENT FINANCIAL STATEMENTS (EMPIRICAL S - Sutarni, Sutarni (Jurnal Ekonomi, 2022)
This study attempts to prove in empirical, the influence of human resources competence (X1), implementation of regional financial accounting system (X2), information technology utilization (X3), the role of internal audit (X4), and internal control system (X5) on the quality of local government financial report (Y) in working units of Lampung central district. Sample in this research is taken directly of the population employees in working units in Lampung central district, by using the purposive sampling method obtained samples from 77 an employees who used as respondents. Methods of analysis in this study is the analysis of multiple linear regression. Analytical tools used in this research is the program SPSS Version 20. The result of this research prove that human resources competence, implementation of regional financial accounting system, information technology utilization, the role of internal audit and internal control system in partial and simultaneous have had a positive impact and significant on the quality of local government financial report in working units of Lampung central district